Sosialisasi Manajemen Risiko dalam Transaksi Perdagangan Berjangka bagi Pemula - Sudrajat, ibadullah Bena Yajna; Santoso, Bowo (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Low awareness of investment risks often leads novice investors into illegal futures trading schemes. This socialisation, conducted at Gedung Kuliah Bersama 1, aimed to equip students with risk management education through the use of MetaTrader demo accounts in collaboration with PT Trijaya Pratama Futures. Through a combination of material presentation and hands-on simulation, participants were encouraged to understand the importance of broker legality and actual market mechanisms. Field results indicated that practicing with demo accounts significantly helped students grasp the concrete function of capital protection features, such as stop-loss orders. Despite some technical device constraints, the activity successfully shifted the participants' perspectives to be more rational, moving beyond a focus on potential profits alone. The integration of regulatory theory and practical simulation serves as a key element in building a healthy financial literacy foundation within the academic environment.